The effects of extreme drought events on the morphometry of shallow lakes: Implications for sediment resuspension and littoral and pelagic zone distribution - Seitz, Carina (2020)
Shallow lakes, because of their depth, are more vulnerable to the effects of wind and changes in precipitation and evaporation that deeper lakes and thus respond more dramatically to extreme climatic events, such as drought. The morphology of shallow lakes influences many of their physical, chemical, biological and sedimentological processes including sediment resuspension. Sediment resuspension can trigger undesired effects such as eutrophication, increase in turbidity, cyanobacterial blooms, and also affects the distribution and extent of the littoral and pelagic zones (habitat distribution) with potentially negative consequences on biodiversity and loss of native species. These problems are an increasing concern in the face of global warming. To understand how changes in lake' morphometry, triggered by extreme drought events influence sediment resuspension and habitat distribution, we studied four shallow lakes located in the southwest of the Argentinean Pampas. Each lake was characterized by its bathymetry, morphometric parameters (including area, shore development, dynamic ratio, critical depth), the spatial distribution of the littoral and pelagic areas, and the effect of the waves on sediment resuspension. We measured the Area and Shore development again during selected extreme drought periods identified through the Standardized Precipitation-Evapotranspiration Index. Then, for the given drought period, we calculated the extent and distribution of littoral and pelagic areas and the critical depth at which sediment resuspension occurred and then estimated the percentage of the lake that would be affected by it. We found that Pampean lakes are profoundly affected by sediment resuspension triggered by wind during extreme dry events. Droughts have different effects depending on lake morphology. Dry periods caused not only a decrease in water volume, but also modified the extension of littoral and pelagic zones and increased sediment resuspension. These results have significant implications for the preservation of these rich ecosystems, especially in the context of global warming.